Los silenciamientos de la ciencia ambiental: una reflexión crítica sobre estructuras de opresión - Cárdenas Támara, Felipe (Nómadas. Critical Journal of Social and Juridical Science, 2007)
The article explores critically and with the support in a research experience developed in various environmental projects in Colombia, the forms of a totalitarian and dogmatic way of making science that is expressed in a biologicist and materialistic science models that dominate environmental research. The dominant scientific model in the field of environmental studies denotes an oppressive relation with other expressions in the knowledge generation. The consequences are that the environmental sciences, due to the predominance of an esquizoid and sicotic scheme of scientific exercise, that ends impoverishing the comprehension of reality and invisibilizing other forms of making science.